2015
DOI: 10.3109/13651501.2015.1031681
|View full text |Cite
|
Sign up to set email alerts
|

Chinese patients with major depression: Do concomitant pain symptoms affect quality of life independently of severity of depression?

Abstract: PPSs were associated with less improvement in QoL in patients receiving treatment for MDD, independent of severity of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…In clinical practice, physicians should assess the severity of headache. Second, according to previous studies, PPS are associated with a poorer quality of life and a poorer treatment outcome of depression [2,4,6]. Moreover, our results showed that patients with migraine with active headache had the lowest remission rate of depression, as compared with patients with migraine with inactive headache and non-migraine subjects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In clinical practice, physicians should assess the severity of headache. Second, according to previous studies, PPS are associated with a poorer quality of life and a poorer treatment outcome of depression [2,4,6]. Moreover, our results showed that patients with migraine with active headache had the lowest remission rate of depression, as compared with patients with migraine with inactive headache and non-migraine subjects.…”
Section: Discussionsupporting
confidence: 75%
“…PPS and depression interact closely [2,3]. Among patients with major depressive disorder (MDD), PPS are common [4,5], and are associated with worse depression, an increased suicidal risk, functional impairment, a poorer quality of life, and a poorer treatment response [26].…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) and pain symptoms may have a shared neurobiological mechanism and may be genetically correlated [ 3 , 4 ]. Among patients with MDD, pain symptoms are common, and are associated with a greater severity of depression, a poorer treatment response, inability to achieve full remission, impaired function, a poorer quality of life, and an increased suicidal risk [ 3 , 5 9 ].…”
Section: Introductionmentioning
confidence: 99%